2018
DOI: 10.1038/s41598-018-20714-5
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Modification of Poly Lactic Acid Solutions to Generate High Quality Electrospun PLA Nanofibers

Abstract: Physical properties of pre-electrospinning polymer solutions play a key role in electrospinning as they strongly determine the morphology of the obtained electrospun nanofibers. In this work, an atmospheric-pressure argon plasma directly submerged in the liquid-phase was used to modify the physical properties of poly lactic acid (PLA) spinning solutions in an effort to improve their electrospinnability. The electrical characteristics of the plasma were investigated by two methods; V-I waveforms and Q-V Lissajo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 48 publications
2
51
0
Order By: Relevance
“…followed a similar strategy, using an atmospheric pressure plasma jet (APPJ) to treat polylactic acid dissolved in dichloromethane and observed 100% bead‐free fibers . In our research group, an extensive study on the effects of NTP exposure on a solution of PCL or PLLA in CHCl 3 and DMF was recently performed . It was found that the plasma was responsible for improving the conductivity of the polymer solution as well as changing the viscosity and pH via the generation of new chemical species without damaging the macromolecular structure of the polymer …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…followed a similar strategy, using an atmospheric pressure plasma jet (APPJ) to treat polylactic acid dissolved in dichloromethane and observed 100% bead‐free fibers . In our research group, an extensive study on the effects of NTP exposure on a solution of PCL or PLLA in CHCl 3 and DMF was recently performed . It was found that the plasma was responsible for improving the conductivity of the polymer solution as well as changing the viscosity and pH via the generation of new chemical species without damaging the macromolecular structure of the polymer …”
Section: Introductionmentioning
confidence: 99%
“…However, the use of NTP to alter the properties of polymeric solutions (for electrospinning) is a field of research that has barely been touched upon. So far, to the best of the author's knowledge, only five research papers have been published that deal with this subject . Shi et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attention and interest in nanofiber technology has substantially grown in the last decades due to their unique properties and many potential biomedical applications such as tissue engineering scaffolds, wound dressings, drug delivery devices as well as many other industrial applications . In the biomedical field, there is a great tendency to use nanofibers generated from biodegradable polymers due to their similarity to native tissues which is believed to result in improved cell interactions and extracellular matrix generation .…”
Section: Introductionmentioning
confidence: 99%
“…Taking this into account, pre‐electrospinning plasma treatment (PEPT) of polymer solutions has already been investigated by several research groups, including ours, as an innovative and environmentally friendly method to change polymer solution properties in an effort to increase the electrospinnability of these solutions . For example, Shi et al have treated polyethylene oxide (PEO) and polyacrylonitrile (PAN) solutions and observed the creation of finer and smoother nanofibers after electrospinning.…”
Section: Introductionmentioning
confidence: 99%